Comparative Study of Nano-chitosan and Synthetic Bactericide Application on Chili Pepper (Capsicum annuum L.) Infected by Xanthomonas campestris - Rizkita R. Esyanti; Nadya Farah; Brahmani D. Bajra; Diah Nofitasari; Ronny Martien; Sunardi Sunardi; Ramadhani Safitri (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Nano-chitosan is considered as a prospective replacement for synthetic bactericides. In this study, the antibacterial activity of nano-chitosan and synthetic bactericides was compared in four chili pepper cultivars (Bianca, Lado, Kiyo, and Tanamo) infected by Xanthomonas campestris. To assess the effect of nano-chitosan and synthetic bactericide on the growth of the X. campestris-infected chili pepper plants, some parameters were observed including the plant height, number of leaves and chlorophyll content. It was shown that nano-chitosan was highly effective in controlling the pathogen infection on Bianca, Lado, and Tanamo, but not significant on Kiyo. The application of synthetic bactericide, however, was effective on Bianca and Lado, but not significant on Kiyo and Tanamo. It was also shown that the application of nano-chitosan can improve the growth of the X. campestris-infected chili pepper plants based on the significant difference on the plant height, number of leaves and chlorophyll content of cultivars tested, especially in Kiyo, Lado, and Tanamo. The application of synthetic bactericide, however, did not significantly improve the growth of the X. campestris-infected chili pepper plants. Nano-chitosan was shown to be effective in reducing the infection of X. campestris and potentially be used as an alternative to synthetic bactericide.